2012
DOI: 10.1371/journal.pone.0050860
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Imaging and Quantification of Carbonic Anhydrase IX Expression as an Endogenous Biomarker of Tumor Hypoxia

Abstract: Carbonic anhydrase IX (CA IX) is a transmembrane protein that has been shown to be greatly upregulated under conditions of hypoxia in many tumor cell lines. Tumor hypoxia is associated with impaired efficacy of cancer therapies making CA IX a valuable target for preclinical and diagnostic imaging. We have developed a quantitative in vivo optical imaging method for detection of CA IX as a marker of tumor hypoxia based on a near-infrared (NIR) fluorescent derivative of the CA IX inhibitor acetazolamide (AZ). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
67
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 47 publications
3
67
0
Order By: Relevance
“…However, despite the availability of ligand-targeted NIR dyes that bind the epidermal growth factor receptor (48), folate receptor alpha (49), CCK2R (50) and PSMA (51), the majority of human cancers still cannot be imaged with a tumor-targeted fluorescent dye. Several reports of CA IX-targeted fluorescent and radioimaging agents have shown the utility of carbonic anhydrase IX targeting ligands for visualization of cancers (38,52,53). Using a different high affinity CA IX ligand, we demonstrate here that a novel CA IX-targeted NIR dye that can illuminate CA IX over-expressing tumors with similar or better results than previous CA IX-fluorescent conjugates.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the availability of ligand-targeted NIR dyes that bind the epidermal growth factor receptor (48), folate receptor alpha (49), CCK2R (50) and PSMA (51), the majority of human cancers still cannot be imaged with a tumor-targeted fluorescent dye. Several reports of CA IX-targeted fluorescent and radioimaging agents have shown the utility of carbonic anhydrase IX targeting ligands for visualization of cancers (38,52,53). Using a different high affinity CA IX ligand, we demonstrate here that a novel CA IX-targeted NIR dye that can illuminate CA IX over-expressing tumors with similar or better results than previous CA IX-fluorescent conjugates.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging probes are designed to detect tissue biomarkers and accumulate directly at the local site of tissue injury, offering rapid multiplexing imaging of various biologic readouts. NIR fluorescent probes have been used effectively to image various disease conditions modeled in preclinical species, including cancer (Weissleder and Ntziachristos, 2003; Montet et al, 2005; Kossodo et al, 2010; Bao et al, 2012), atherosclerosis (Chen et al, 2002; Deguchi et al, 2006), cardiac pathologies (Nahrendorf et al, 2007; Sosnovik et al, 2007), arthritis (Wunder et al, 2004; Peterson et al, 2010), central nervous system demyelination (Eaton et al, 2013), and osteoarthritis (Vermeij et al, 2014). Many of these same fluorescent imaging probes are currently being examined for their utility in toxicology/safety screening (Peterson, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in optical imaging and near-infrared (NIR) probes (Weissleder and Ntziachristos, 2003; Korideck and Peterson, 2009; Krautz-Peterson et al, 2009; Kossodo et al, 2010; Peterson et al, 2010; Bao et al, 2012; Lin et al, 2012; Zhang et al, 2012; Eaton et al, 2013; Daghighi et al, 2014) have shown the benefit of biologic, rather than phenotypic or anatomic, readouts in preclinical drug efficacy research. Although imaging of preclinical models of safety/toxicology has not been pursued extensively to date, the ability to use fluorescent imaging probes that detect and quantify a variety of biologic activities has considerable potential in this area as well (Amoozegar et al, 2012; Shuhendler et al, 2014; Peterson, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…CA IX has proven useful as a biomarker of hypoxic regions in formalin fixed, paraffin embedded tissues [18][19][20][21]. The identification by immunohistochemistry of hypoxia-related tissue factors CA IX and VEGF have been shown to be useful in characterizing patient outcome in various tumor types [14,17], but we are aware of only one previous study reporting CA IX expression in ependymomas.…”
Section: Discussionmentioning
confidence: 99%